Willingness of pregnant and postpartum women who use marijuana and/or cannabidiol to participate with their offspring in long-term cohort studies: an exploratory study - Varma, Deepthi S.; Goodin, Amie J.; Goldberger, Bruce A.; Roussos-Ross, Kay (Frontiers in Psychiatry, 2025)
BackgroundPrevalence of marijuana and cannabinoid use is increasing among reproductive-age women. There are uncertainties regarding long-term impacts of marijuana and/or cannabinoid exposure among pregnant women and their offspring. Longitudinal cohort studies of marijuana and/or cannabinoid exposed mother-infant dyads is the best way to ascertain the long-term impacts. However, previous studies have shown enrollment, and long-term retention are challenging in substance-exposed women.ObjectivesThis study explores the willingness of pregnant and postpartum women who use marijuana and/or cannabidiol to participate with their offspring in long-term cohort studies.MethodsWe conducted 4 focus group discussions and one individual one-on-one interview with a total of 17 pregnant or postpartum women using an IRB approved interview guide. All interviews were audiotaped, transcribed and analyzed using the computer assisted qualitative data analysis software Atlas ti™. We used a deductive content analysis approach and utilized consensus coding procedures.ResultsMarijuana and/or cannabinoid-exposed pregnant women are willing to participate in long-term research studies with their babies if they can build a trusting relationship with the research staff and are confident of their anonymity, as protection from negative consequences was a key concern. They would also like to understand in detail what type of data are collected, when and who all will see it and what will be done with the data before they provide the consent. All participants agreed that incentives are important and had various suggestions regarding the type and frequency of incentivization.ConclusionThe concerns and needs of marijuana and/or cannabinoid-exposed pregnant women recruited for research should be considered carefully in designing study protocols.